Locally Trapping the C-C Chemokine Receptor Type 7 by Gene Delivery Nanoparticle Inhibits Lymphatic Metastasis Prior to Tumor Resection - An, Sai (Small, 2019)
Triple negative breast cancer (TNBC) is the most aggressive breast cancer subtype. Currently, no targeted treatment is available for TNBC, and the most common clinical therapy is tumor resection, which often promotes metastasis risks. Strong evidence suggests that the lymphatic metastasis is mediated by the C-C chemokine receptor type 7 (CCR7)/C-C motif chemokine ligand 21 crosstalk between tumor cells and the lymphatic system. It is hypothesized that CCR7 is a key immune modulator in the tumor microenvironment and the local blockade of CCR7 could effectively inhibit TNBC lymphatic metastasis. Accordingly, a plasmid encoding an antagonistic CCR7 affinity protein-CCR7 trap is delivered by tumor targeting nanoparticles in a highly metastatic 4T1 TNBC mouse model. Results show that CCR7 traps are transiently expressed, locally disrupt the signaling pathways in the tumor site, and efficiently inhibit TNBC lymphatic metastasis, without inducing immunosuppression as observed in systemic therapies using CCR7 monoclonal antibody. Significantly, upon applying CCR7 trap therapy prior to tumor resection, a 4T1 TNBC mouse model shows good prognosis without any further metastasis and relapse. In addition, CCR7 trap therapy efficiently inhibits the lymphatic metastasis in a B16F10 melanoma mouse model, indicating its great potential for various metastatic diseases treatment.